(untitled) (Journal of Management and Educational Sciences, 2024)
This research aims to examine the effects of organizational-managerial motivation practices on teachers’ productivity, according to teachers’ opinions. Relational screening model was used in the research. According to the results of the research, productivity and organizational-managerial motivation perception levels were above average. In the research, when examined according to gender; It has been revealed that the productivity of male teachers is higher than that of female teachers. On the other hand, it was revealed that organizational-managerial motivation and productivity perceptions do not differ between men and women. In addition, no statistical difference was found between the organizational-managerial motivation scale and productivity scale and the arithmetic averages of age and professional experience groups. Another result of the research is that teachers’ organizational-managerial motivation perceptions significantly predict their productivity perceptions. In other words, a 100-unit increase in teachers’ organizational-managerial motivation dimension increases their productivity perceptions by 48.8%.